2006
DOI: 10.1097/01.ccm.0000196216.49407.ee
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-flow signatures of central-airway mucus plugging

Abstract: Four newly observed signs were recorded that may serve to identify occult central airway mucus plugging in the ventilated asthmatic patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…This could be due to cumulative effects of the blending of cellular contents, mucus, and protein exudates. [8] Kuyper et al . investigated the characteristic of mucus plugging in fatal asthma patients and it was observed that cellular content was a mixture of migratory inflammatory cells and shed epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to cumulative effects of the blending of cellular contents, mucus, and protein exudates. [8] Kuyper et al . investigated the characteristic of mucus plugging in fatal asthma patients and it was observed that cellular content was a mixture of migratory inflammatory cells and shed epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Despite positive reports of the benefits of bronchoscopy and lavage in severe asthmaticus, its use continues to be documented only in case reports[489] and some observational studies. [9] Therefore, concrete evidence supporting the effectiveness of this potentially beneficial therapy is still awaited.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we could not use any methods to measure the volume of secretions removed from the airway or analysis of the mucus mass displacement. These techniques are considered to be more objective ways to assess the technique's effects; (6,30,33) this lack may have limited the assessment of the possible benefits from this technique. Considering that this study had a small sample size and only assessed shortterm outcomes, larger sample sizes and assessment of long-term clinical outcomes are required before our findings can be extrapolated.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes this phenomenon is difficult to appreciate. 26 Mouthward migration of mucus is favored by ventilatory pattern; high tidal volume, (low) PEEP, extended inspiratory to expiratory time ratio and square wave gas flow profile appear to be beneficial for secretion elimination.…”
Section: Mechanical Interventionsmentioning
confidence: 96%